Occupational Therapy Making Salted Eggs On Improving Ability And Independence Of ODGJ - Serly Agustina Dewi Saputri; Ritalia Monika Kakak; Roslina Ambu Kaka; Rindia Agusta; Dhita Kurnia Sari (Journal for Quality in Public Health, 2023)
The need for social interaction is a basic human need, in minimizing social welfare problems, especially for people with disabilities, namely people with mental disorders, the role of an agency is needed, one of which is the Ngletih Community Health Center in Kediri. However, at the Ngletih Mental Health Center posyandu there are no activities that can improve the ability and independence of ODGJ. Seeing this problem, we provide a solution by providing occupational therapy as an effort to increase the independence of ODGJ at the Ngletih Health Center. The research activity aims to determine the increase in the ability and independence of ODGJ before and after being given occupational therapy to make salted eggs. The research was conducted at the Ngletih Mental Health Center Posyandu with 13 people who came. The method used is pre-experiment research with a one-group pretest-posttest design, data collection using questionnaires, analysis techniques using pre post data scale statistics. The results of the research that have been carried out produce an average value before treatment is 50.76 while the average ability to make salted eggs ODGJ after being given treatment or occupational therapy is 81.15 this proves that the ability to make salted eggs increases after the provision of salted egg making occupational therapy, so it can be concluded that the provision of occupational therapy to make salted eggs can increase the independence and ability of ODGJ in the Ngletih Puskesmas Mental Health Post.